a, \(\left(a+b\right)^2=\left(a+b\right)\left(a+b\right)=a^2+ab+ab+b^2=a^2+2ab+b^2\)
b, \(\left(a-b\right)^2=\left(a-b\right)\left(a-b\right)=a^2-ab-ab+b^2=a^2-2ab+b^2\)
c, \(a^2-b^2=a^2+ab-ab-b^2=a\left(a+b\right)-b\left(a+b\right)=\left(a+b\right)\left(a-b\right)\)
\(a,\left(a+b\right)^2\\ =\left(a+b\right)\left(a+b\right)\\ =a^2+ab+b^2+ab\\ =a^2+2ab+b^2.\)
\(b,\left(a-b\right)^2\\ =\left(a-b\right)\left(a-b\right)\\ =a^2-ab+b^2-ab\\ =a^2-2ab+b^2.\)
\(c,a^2-b^2\\ =a^2+ab-ab-b^2\\ =a\left(a+b\right)-b\left(a+b\right)\\ =\left(a-b\right)\left(a+b\right).\)